2015
DOI: 10.3168/jds.2014-8902
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of coagulation, curd firming, and syneresis of milk from Sarda ewes

Abstract: This study investigated the modeling of curd-firming (CF) over time (CF(t)) of sheep milk. Milk samples from 1,121 Sarda ewes from 23 flocks were analyzed for coagulation properties. Lactodynamographic analyses were conducted for up to 60 min, and 240 CF individual observations from each sample were recorded. Individual sample CFt equation parameters (RCT(eq), rennet coagulation time; CF(P), asymptotic potential value of curd firmness; k(CF), curd-firming instant rate constant; and k(SR), curd syneresis instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 36 publications
5
51
1
Order By: Relevance
“…Interestingly, CLA supply negatively affected the milk coagulation properties of bovine and ovine milk (Bittante et al, 2014;Vacca et al, 2015). Using the same milk samples as those collected for the present study, Cesaro and Schiavon (2015) found that rumenprotected CLA supplementation increased rennet coagulation time and time to curd firmness of 20 mm (k 20 ), and reduced curd firmness 30 min after enzyme addition (a 30 ).…”
Section: Cheese Manufacturing and Nutrient Recoverymentioning
confidence: 63%
“…Interestingly, CLA supply negatively affected the milk coagulation properties of bovine and ovine milk (Bittante et al, 2014;Vacca et al, 2015). Using the same milk samples as those collected for the present study, Cesaro and Schiavon (2015) found that rumenprotected CLA supplementation increased rennet coagulation time and time to curd firmness of 20 mm (k 20 ), and reduced curd firmness 30 min after enzyme addition (a 30 ).…”
Section: Cheese Manufacturing and Nutrient Recoverymentioning
confidence: 63%
“…() and Vacca et al . (). Groups of ewes from each farm ranged in number from 17 to 56 and, from each sire, ranged from one to 28.…”
Section: Methodsmentioning
confidence: 97%
“…All the ewes were officially registered in the Sarda breed flock book and they were included in the selection scheme of the Sarda breed. Farms, animals, and sampling have been reported in Pazzola et al (2014) and Vacca et al (2015). Briefly, ewe parity ranged from 1 (primiparous) to 9, and ewes were sampled between 2 and 7 mo after parturition.…”
Section: Animals and Samplingmentioning
confidence: 99%